Influence of Compensation and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable - Safia, Fidia Okti; Prabowo, Heri; Violinda, Qristin (PT. Riset Press International, 2025)
This study aims to determine the effect of compensation and work motivation on employee performance with job satisfaction as an intervening variable on PT. Mitra Pengusaha Indonesia. This study uses a quantitative research method. The population used in the study were employees of PT. Mitra Pengusaha Indonesia in 2024 and the sample used was 100 employees with a simple random sampling technique. The sampling technique used probability techniques. Data analysis using SmartPLS. The results of this study indicate that there is a negative and significant effect between Compensation (X1) on Job Satisfaction (Z). Work Motivation (X2) has a positive and significant effect on Job Satisfaction (Z). The results of this study highlight the importance of motivation in employees of PT. Mitra Pengusaha Indonesia. So thus motivation plays a very important role in employee performance, on the other hand compensation does not affect performance. Compensation requires a more strategic approach in order to have a significant impact. Companies can provide compensation to employees transparently and adjusted to the workload borne by so that it becomes effective as part of a strategy to increase employee job satisfaction at PT. Mitra Pengusaha Indonesia.